Differential upregulation of host cell protein kinases by the replication of α-, β- and γ-herpesviruses provides a signature of virus-specific signalling. (20th January 2020) - Marschall, Manfred; Strojan, Hanife; Kiener, Richard; Wangen, Christina; Sonntag, Eric; Müller, Regina; Zeitträger, Isabel; Wagner, Sabrina; Stamminger, Thomas; Milbradt, Jens; Behrends, Uta; Körber, Nina; et al.
Abstract : Infections with human herpesviruses share several molecular characteristics, but the diversified medical outcomes are distinct to viral subfamilies and species. Notably, both clinical and molecular correlates of infection are a challenging field and distinct patterns of virus–host interaction have rarely been defined; this study therefore focuses on the search for virus-specific molecular indicators. As previous studies have demonstrated the impact of herpesvirus infections on changes in host signalling pathways, we illustrate virus-modulated expression levels of individual cellular protein kinases. Current data reveal (i) α-, β- and γ-herpesvirus-specific patterns of kinase modulation as well as (ii) differential levels of up-/downregulated kinase expression and phosphorylation, which collectively suggest (iii) defined signalling patterns specific for the various viruses (VSS) that may prove useful for defining molecular indicators. Combined, the study confirms the correlation between herpesviral replication and modulation of signalling kinases, possibly exploitable for the in vitro characterization of viral infections.